Low-Frequency Coherent Raman Spectroscopy Using Spectral-Focusing of Chirped Laser Pulses - Tani, Masahiko; Hibi, Masakazu; Yamamoto, Kohji; Yamaguchi, Mariko; Estacio, Elmer S.; Que, Christopher T.; Hangyo, Masanori (IntechOpen, 2012)
None